Global patterns and trends of carbon monoxide poisoning: A comprehensive spatiotemporal analysis using joinpoint regression and ARIMA modeling, 1990–2021 - Weiguang Wang; Yongai Ling; Xianwei Xiong; Jiajie Zhou (PLoS ONE, 2025)
Background Carbon monoxide (CO) poisoning causes approximately 41,000 deaths annually worldwide despite being preventable. Previous studies focused primarily on mortality alone, lacked systematic socio-demographic analysis, and provided no predictive models. This study comprehensively analyzes global CO poisoning patterns using spatiotemporal methods to inform evidence-based prevention strategies. Methods We analyzed Global Burden of Disease Study 2021 data from 204 countries (1990–2021) for age-standardized incidence, mortality, and disability-adjusted life years (DALYs). Joinpoint regression identified temporal trends with statistical precision, spatial statistics quantified geographic clustering, and ARIMA modeling projected trends through 2050. We examined associations with socio-demographic index (SDI) across regions and countries. Results Global age-standardized incidence rates decreased significantly by 35.1% from 12.13 (95% UI: 8.30–17.00) to 7.87 (95% UI: 5.54–10.81) per 100,000 population (annual percentage change: −1.16%, 95% UI: −1.35% to −0.96%, p < 0.001). Mortality rates declined more dramatically by 53.9% from 0.76 (95% UI: 0.66–0.91) to 0.35 (95% UI: 0.24–0.40) per 100,000 (annual change: −2.79%, 95% UI: −3.14% to −2.44%, p < 0.001). DALY rates showed the steepest reduction of 59.5% from 37.59 (95% UI: 31.75–44.76) to 15.22 (95% UI: 10.67–17.57) per 100,000 (annual change: −3.18%, 95% UI: −3.51% to −2.84%, p < 0.001). Eastern Europe demonstrated the highest burden (37.98 per 100,000 in 2021). Males experienced significantly higher mortality than females (0.50 vs 0.20 per 100,000, p < 0.001). SDI analysis revealed an inverted U-shaped relationship (Spearman’s r = 0.76, p < 0.001), with peak burden at moderate development levels (SDI: 0.6–0.7). Conclusions These findings directly address previous research gaps by demonstrating: (1) faster mortality decline than incidence decline indicates improved global treatment capabilities; (2) the SDI-burden relationship identifies moderate-development countries as priority intervention targets; (3) significant male predominance (2.5-fold higher mortality) supports gender-specific prevention programs; and (4) persistent Eastern European hotspots require targeted infrastructure improvements. Predictive models forecast continued decline through 2050 and enable evidence-based healthcare planning. This comprehensive analysis provides the first multi-dimensional global assessment, offering crucial evidence for differentiated prevention strategies worldwide.